Faculty and Student Partnerships in the Scholarship of Teaching and Learning: Evaluation of an Institutional Model (Teaching and Learning Inquiry, 2022)
We present the design and evaluation of an institutional support model for the Scholarship of Teaching and Learning (SoTL): the SoTL Seed Program. In this model, faculty from across disciplines partner with graduate students with expertise in educational and social science methodologies to implement SoTL investigations. We interviewed and obtained feedback from both faculty and graduate students about their experiences. A qualitative approach based on grounded theory suggests that organized and sustained partnership between faculty and graduate students offers a viable institutional framework to support SoTL across academic disciplines. In our institution, partnerships in SoTL have resulted in facilitating academic and professional development for both faculty and graduate students, establishing communities of practice for SoTL, and providing infrastructure for systematic engagement with SoTL.